2014
DOI: 10.1177/0040517514525881
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of para-aramid fabric impregnation with shear thickening fluid on quasi-static stab resistance

Abstract: The main research objective of this study was to investigate the effect of the impregnation of Twaron® fabric with various shear thickening fluids (STFs) on the stab resistance at quasi-static conditions—being the main parameter characterizing the future application of the impregnated textiles in the scope of the new functionality of the elaborated protection of the multi-layer system. It was found that the STF/Twaron® fabric composites required significantly higher loading than the untreated fabric to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 11 publications
0
12
0
2
Order By: Relevance
“…The major role of materials used for stab and spike protection is to prevent the weapon from passing through them and penetrating into the skin and flesh of the wearer. [18][19][20][21] Stab resistant body armor systems should provide the required protection from knives and other edged-weapons, whereas spike resistant body armor systems protect from pointed-weapons, while ensuring the unrestricted movement of the wearer. The body armor should protect the vital organs, in particular the heart, liver, lungs, spine, kidneys, and spleen 21,22 in the case of attacks using various weapons.…”
Section: Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major role of materials used for stab and spike protection is to prevent the weapon from passing through them and penetrating into the skin and flesh of the wearer. [18][19][20][21] Stab resistant body armor systems should provide the required protection from knives and other edged-weapons, whereas spike resistant body armor systems protect from pointed-weapons, while ensuring the unrestricted movement of the wearer. The body armor should protect the vital organs, in particular the heart, liver, lungs, spine, kidneys, and spleen 21,22 in the case of attacks using various weapons.…”
Section: Protectionmentioning
confidence: 99%
“…It was suggested that a mass fraction of 38% in STF is the optimal for knife and stab protection. The effect of impregnating Twaron fabric with various STF on the quasi-static stab resistance properties was evaluated by Zielinska et al 19 It was observed that the combination of STF/Twaron fabric composites required significantly higher loading than the untreated fabric to achieve spike penetration. In the composite fabric tests, the spike did not fully puncture the material.…”
Section: Textile Solutionsmentioning
confidence: 99%
“…[10][11][12] Numerous studies have made a great effort towards the optimal design of woven fabrics with excellent puncture performances. [13][14][15][16][17][18] A series of process parameters, such as the STF concentration, average particle size of silica, particle hardness, dispersing media, solvent ratio and padding pressure, was systematically evaluated. Majumdar et al 19 found that higher silica concentrations, higher padding pressures and lower solvent ratios lead to higher puncture energy absorption in STF-treated fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Gürgen et al 32 has thoroughly reviewed the applications of STF for protective applications and therefore, the present work will only briey describe this aspect. STF has been explored and used for low velocity impact applications, 81,82 stab and spike protection [83][84][85][86][87][88][89][90][91][92] as well as for high velocity ballistic impact applications. 17,93,94 Shear thickening uid (STF) is a non-Newtonian uid having two phases, namely dispersed phase and dispersion medium.…”
Section: Use Of Shear Thickening Uids (Stf)mentioning
confidence: 99%